Situation Report: Bulgaria, 28 August 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Bulgaria and the Romanian 25th Anniversary Ambassador in Bucharest Replaced Dimitrov Prizes Awarded Bulgaria Protest Congolese Action Miscellaneous Bashev on Holiday in East Germany Economic Co-operation with Denmark Bulgarian-Hungarian Co-Operation Lebanese Delegation in Sofia